(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: In practice anesthesiologists do not always respond immediately to mothers’ needs, which can impact the quality of care. To address this issue, this study aims to evaluate the effectiveness of having a trained anesthetic nurse manage epidural analgesia in improving maternal satisfaction, pain relief quality, and not affecting the mother’s pushing efforts. Research objects and methods: Retrospective of 3986 pregnancies over 36 weeks gestation who received epidural analgesia for pain control were reviewed during (n = 3986) under the cared for by an anesthetist nurse at Vinmec healthcare system including 7 hospitals: Vinmec Time City, Hai Phong, Ha Long, Phu Quoc, Nha Trang, Da Nang, Center Park. Results: Among them 3986 women received care from a anesthetists nurse between January 2023 and June 2024, there were 70 cases (1.8%) of pain during labor requiring catheter adjustment and management with a satisfaction score assessed by the midwife of less than 4 points. Having an anesthetic nurse resulted in higher maternal satisfaction scores compared to before, with no adverse effects on maternal, neonatal, or epidural-related complications. Conclusion: These findings suggest that assigning an anesthetic nurse to manage epidural analgesia may enhance maternal satisfaction and potentially improve overall care quality.